Ministry of Works and Labour, 1960-1963. - Buganda Government
This file contains correspondence some of which are written by S. K. Masembe Kabali, the parliamentary secretary Ministry of Works and La bour and others addressed to him mainly concerning trade, transport, un employment etc as well as reports on S. K. Masembe Kabali's tours condu cted in the conduct of the ministrial activities.
AR/BUG/1/2
Luganda and English.
Shelf no. 1